Preparation, characterization and application of zeolite A/Metal oxides nanocomposites for adsorption of arsenic and lead from aqueous solutions - Alswat, Abdullah Abdullah Naji (2017)
How to completely remove toxic metals from water is still a serious challenge and is the mission that faces researchers and scientists today. In this research, zeolite A/copper oxide (CuO), zeolite A/zinc oxide (ZnO) and zeolite A/iron oxide (Fe3O4) nanocomposites (NCs) were prepared via a co-precipitation method. The effect of weight percentage (wt. %) of these metal oxides (MOs) to the zeolite was investigated to obtain the optimum MOs distribution and surface area. Zeolite-MOs nanocomposites were characterized by Fourier transform infrared (FT-IR) spectroscopy, powder X-ray diffraction (PXRD) and energy dispersive X-ray fluorescence spectrometry (EDXRF). Nitrogen sorption isotherm was used to determine the specific surface areas, pore size and pore volume, while the surface was morphologically observed by transmission electron microscopy (TEM) and field emission scanning electron microscopy (FESEM). The batch adsorption process was used to study the applicability of the nanocomposites to adsorb lead Pb(II) and arsenic As(V) from aqueous solutions. The effects of the adsorbent dosage, pH, initial metals concentration and contact time on the adsorption process wereinvestigated. XRD patterns showed that MOs peaks intensity increased as the intensities of zeolite peaks decreased. TEM images indicated a good distribution of MOs-nanoparticles (NPs) onto the zeolite framework and the cubic structure of the zeolite was maintained. The average particle size of MOs-NPs loaded on the surface of the zeolite was less than 20 nm. The highest surface area was at 8, 5, and 15 wt. % for zeolite A/CuO, zeolite A/ZnO and zeolite A/Fe3O4 NCs, respectively. Results revealed that in 30 minutes, 0.15 g and at pH 5, zeolite A/Fe3O4, zeolite A/ZnO and zeolite A/CuO NCs were able to adsorb 98.2, 93.1 and 83.7% of Pb(II) and 96.8 , 90.1 and 81.3% of As(V), respectively from100 mg/L aqueus solutions. The Langmuir isotherm model showed higher correlation coefficients and provided better agreement with the experimental data, while the adsorption kinetic followed the pseudo-second-order . The sorbents showed an economical and effective way adsorb toxic metals due to their ambient operation conditions, low-energy consumption and facile regeneration capability.